The influence of regional original revenues, balancing funds and capital expenditures on the financial performance of regency/city regional governments of East Java Province - Moehammad Budi Widajanto; Pinky Pininta Dewi; Rr. Farrah Dipta Ayu Anggraeni (Indonesia Accounting Research Journal, 2022)
This study aims to determine and obtain empirical evidence of the effect of Regional Original Revenues, Balancing Fund and Capital Expenditure partially and simultaneously on the Financial Performance of Regency/City Governments in East Java Province. The type of research used is quantitative with a causal associative approach. The research data used is secondary data. The sampling technique used in this research is saturated sampling. The population in this study is the East Java Province Regional Budget Realization Report of 38 districts/cities for 3 fiscal years 2018-2020. The sample in this study was all 38 districts/cities of East Java Province consisting of 29 districts and 9 cities with a research period of 3 years. The analytical method used is multiple linear regression. The results of this study indicate that partially the Regional Original Revenues has a positive effect on the financial performance of the regional government, the Balancing Fund has a negative effect on the financial performance of the regional government, and Capital Expenditure have a negative effect on the financial performance of the regional government. Simultaneous test results show that Regional Original Revenues, Balancing Fund and Capital Expenditure together have a significant effect on the Financial Performance of the Regency/City Government of East Java Province.